Neonatal feeding associated with overweight and obesity in children and adolescents of Cuenca, Ecuador - Carlos Alberto Román Collazo; Verónica Cabrera Castro; Diego Paul Andrade Campoverde; Mónica Susana Flores García (Universidad de Ciencias Médicas de La Habana, 2018)
ABSTRACT Introduction: Inadequate feeding in the neonatal stage is associated with the appearance of metabolic diseases in later ontogenetic periods. Objective: To associate breastfeeding and weaning with overweight and obesity in children and adolescents in the Cesar Dávila Andrade Cuenca-Ecuador Educational Unit, from october 2016 to march 2017. Material and Methods: Descriptive, associative and empirical type, during the period November 2016 to January 2017 in Cuenca, province of Azuay, Ecuador. The probabilistic sampling by conglomerates of equal proportions selected 137 children and adolescents from 5 to 18 years of age. A questionnaire was applied that collected sociodemographic and breastfeeding data and ablation. Measurements of weight and height were made with the calculation of the Body Mass Index. The data were processed by descriptive statistics (mean, standard deviation), inferential (T Test, X2) and bivariate correlations (X2, odds ratio) and binary logistic regression using SPSS 23.0 Results: Breastfeeding for less than six months, the introduction of food early and mild physical activity are factors that increase the risk of overweight and obesity in more than 3 times each in children and adolescents. Conclusion: Breastfeeding and weaning are associated with overweight and obesity from early stages of human development. The explanatory value they have in children and adolescents is relevant, suggesting their use in educational and preventive health programs. Keywords: breastfeeding, weaning, overweight, obesity, infant nutrition, metabolic programming